2022
DOI: 10.1021/acsaem.2c02161
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Analysis of Triple-Cation Perovskite Solar Cells by Electrochemical Impedance Spectroscopy

Abstract: In this work, the electrical properties of different triple-cation compositions with the formula Cs0.05FA1–X MA X Pb­(I1–X Br X )3 have been analyzed using electrochemical impedance spectroscopy. The perovskite solar cells were subjected to ambient conditions to compare their results in terms of ambient degradation. Their morphology, optical properties, and photovoltaic performance were characterized. We analyzed the causes and effects of ambient degradation mechanisms on the devices. Electrochemical processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…However, these materials are not exempt from moisture-induced degradation without further engineering-several degradation pathways have been described. [65][66][67] The organic HSL in conventional-architecture (n-i-p) PSCs is also known to degrade through exposure to ambient atmosphere. spiro-OMeTAD, for example, is among the most commonly employed HSLs in conventional-architecture devices.…”
Section: Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, these materials are not exempt from moisture-induced degradation without further engineering-several degradation pathways have been described. [65][66][67] The organic HSL in conventional-architecture (n-i-p) PSCs is also known to degrade through exposure to ambient atmosphere. spiro-OMeTAD, for example, is among the most commonly employed HSLs in conventional-architecture devices.…”
Section: Stabilitymentioning
confidence: 99%
“…However, these materials are not exempt from moisture‐induced degradation without further engineering—several degradation pathways have been described. [ 65–67 ]…”
Section: Introductionmentioning
confidence: 99%
“…Their energy disorder and reduced carrier concentrations seriously affect the PCE of a device [9]. In addition, these defects may cause problems such as ion migration and related current hysteresis, as well as the degradation of the device due to environmental factors, especially in the case of lead-free perovskite solar cells [10,11]. Therefore, high-quality perovskite films with large crystal sizes and a reduced grain boundary density are necessary for efficient and stable solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite solar cells (PSCs) have recently emerged as highly promising candidates for next-generation photovoltaics, displaying remarkable progress in power conversion efficiencies (PCEs) that approach 26.1% within a relatively short time span of less than a decade. The general APbX 3 structure of lead halide perovskites allows for variations in both the A site cations and the X site halide anions, providing a means to adjust the material properties. , Numerous studies have highlighted the advantages of incorporating mixed cations and/or anions to finely tune the optoelectronic properties of the halide perovskite structure. Compared to the conventional methylammonium lead iodide (MAPbI 3 ), mixed-cation perovskites offer the ability to obtain high efficiencies while achieving enhanced stability. By introducing a small amount of CsI into the formamidinium (FA) and methylammonium (MA) (MA/FA) mixture solutions, triple-cation PSCs can be fabricated. , Yang et al investigated the impact of cesium (Cs) on the chemical complexity of methyl-free ammonium metal halide perovskites (MHPs) and found that a relatively high Cs component ratio (approximately 30%) promotes the formation of the pure photoactive α phase. However, for MHPs to achieve high photovoltaic performance, Cs doping should be conducted at a moderate ratio .…”
Section: Introductionmentioning
confidence: 99%
“…1−6 The general APbX 3 structure of lead halide perovskites allows for variations in both the A site cations and the X site halide anions, providing a means to adjust the material properties. 7,8 Numerous studies have highlighted the advantages of incorporating mixed cations and/or anions to finely tune the optoelectronic properties of the halide perovskite structure. 9−11 Compared to the conventional methylammonium lead iodide (MAPbI 3 ), mixed-cation perovskites offer the ability to obtain high efficiencies while achieving enhanced stability.…”
Section: Introductionmentioning
confidence: 99%